2006
DOI: 10.1111/j.1524-475x.2005.00084.x
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional cryosurgery enhances the involution of recalcitrant auricular keloids: a new clinical approach supported by experimental studies

Abstract: To explain the mechanism of action of a novel intralesional cryoprobe, thermal behavior measurements, and histological studies were performed in swine muscle specimens after intralesional cryosurgery ex vivo. Slow cooling (20 degrees C/min) and thawing (25 degrees C/min) rates, end temperature of -30 degrees C, produced 8 mm wide diffuse coagulative-type necrosis and a 3 mm-wide transition zone around the cryoprobe. In contrast, contact cryosurgery showed fast cooling and thawing rates (80 degrees C/min) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
102
0
9

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(118 citation statements)
references
References 41 publications
7
102
0
9
Order By: Relevance
“…Other studies have confirmed these good results, showing that intralesional cryosurgery reduced scar volume, hardness, colour and subjective symptoms of pain, tenderness, itching and discomfort [15,16]. Studies have also highlighted the fact that keloids on black skin exhibit less depigmentation following intralesional cryosurgery compared to the contact method [18].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Other studies have confirmed these good results, showing that intralesional cryosurgery reduced scar volume, hardness, colour and subjective symptoms of pain, tenderness, itching and discomfort [15,16]. Studies have also highlighted the fact that keloids on black skin exhibit less depigmentation following intralesional cryosurgery compared to the contact method [18].…”
Section: Discussionsupporting
confidence: 52%
“…This 14-gauge, stainless steel needle has a sharp-cutting, sealed, distal tip that enhances penetration into the hard, rubbery hypertrophic scar without the need for a stylet and causes less tissue trauma than might occur with an open cutting tip [6,7]. The inbuilt cryogen safety vent situated at the proximal end of the needle enables the creation of a uniform ice cylinder along the entire length of the needle and prevents direct spillage of liquid nitrogen onto the surrounding normal skin, which might occur with open-tip needles [15,16]. …”
Section: Discussionmentioning
confidence: 99%
“…1). This new and novel method has been extensively employed to treat hypertrophic scars and keloids (HSK) [10][11][12][13][14][15][16]. The cryoneedle which is inserted into the core of the scar is connected by an adaptor to a cryogun filled with liquid nitrogen, which is introduced into the cryoprobe thereby freezing the scar tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The intralesional cryosurgery technology (CryoShape, Etgar Group Ltd., Kfar Saba) [10][11][12][13][14][15][16] is comprised of a 14-gauge, straight, double-lumen needle with a sharp-cutting sealed distal tip and a safety vent (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the frequency of both ear piercing and otoplasty, the ear is probably the most frequent area [6] . These keloids are responsible for cosmetic disfigurement [7] . Numerous treatments have been utilized for keloids including surgical excision, intralesional corticosteroid injection, intralesional botulinum toxin A injection, radiotherapy, laser therapy, cryotherapy and classical and intralesional cryosurgery [8,9,10] .…”
Section: Introductionmentioning
confidence: 99%